Generalized Hypergeometric Functions & Meijer G -Function - 16.8 Differential Equations
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
16.8.E4 | z^{q}D^{q+1}w+\sum_{j=1}^{q}z^{j-1}(\alpha_{j}z+\beta_{j})D^{j}w+\alpha_{0}w = 0 |
(z)^(q)* (D)^(q + 1)* w + sum((z)^(j - 1)*(alpha[j]*z + beta[j])*(D)^(j)* w , j = 1..q)+ alpha[0]*w = 0 |
(z)^(q)* (D)^(q + 1)* w + Sum[(z)^(j - 1)*(Subscript[\[Alpha], j]*z + Subscript[\[Beta], j])*(D)^(j)* w , {j, 1, q}, GenerateConditions->None]+ Subscript[\[Alpha], 0]*w == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
16.8.E5 | z^{q}(1-z)D^{q+1}w+\sum_{j=1}^{q}z^{j-1}(\alpha_{j}z+\beta_{j})D^{j}w+\alpha_{0}w = 0 |
(z)^(q)*(1 - z)*(D)^(q + 1)* w + sum((z)^(j - 1)*(alpha[j]*z + beta[j])*(D)^(j)* w , j = 1..q)+ alpha[0]*w = 0 |
(z)^(q)*(1 - z)*(D)^(q + 1)* w + Sum[(z)^(j - 1)*(Subscript[\[Alpha], j]*z + Subscript[\[Beta], j])*(D)^(j)* w , {j, 1, q}, GenerateConditions->None]+ Subscript[\[Alpha], 0]*w == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |